Recent Progress in “Water-in-Salt” Electrolytes Toward Non-lithium Based Rechargeable Batteries - Wang, Yuyan; Meng, Xiaotang; Sun, Jinfeng; Liu, Yang; Hou, Linrui (Frontiers in Chemistry, 2020)
Aqueous non-lithium based rechargeable batteries are emerging as promising energy storage devices thanks to their attractive rate capacities, long-cycle life, high safety, low cost, environment-friendliness and easy assembly conditions. However, the aqueous electrolytes with high ionic conductivity are always restricted by their intrinsically narrow electrochemical window. Encouragingly, the highly concentrated “water-in-salt” (WIS) electrolytes can efficiently expand the stable operation window, which brings up a series of aqueous high-voltage rechargeable batteries. In the mini review, we mainly summarize the latest progress and contributions of various aqueous electrolytes for non-lithium (Na+, K+, Zn2+, Mg2+ and Al3+) based rechargeable batteries, and give a brief exploration of operating mechanisms of WIS electrolytes in expanding electrochemically stable windows. Besides, the challenges and prospects are also proposed for WIS electrolytes toward aqueous non-lithium rechargeable metal ion batteries.